Adverse Childhood Experiences Influence Development of Pain During Pregnancy. Issue 2 (June 2016) - Drevin, J.; Stern, J.; Annerbäck, E.M.; Peterson, M.; Butler, S.; Tydén, T.; Berglund, A.; Larsson, M.; Kristiansson, P.
Abstract : ( Acta Obstet Gynecol Scand. 2015;94:840–846) Assessing adverse childhood experience (ACE) is a way of measuring a wide range of traumatic events that might take place before an individual is 18 years of age. These traumas may include emotional, physical, and sexual abuse as well as various household dysfunctions. Adverse childhood experiences are currently believed to lead to impaired social, emotional, and cognitive development.